The Use of Limestone Sand for the Seismic Base Isolation of Structures - Ivan Banović; Jure Radnić; Nikola Grgić; Domagoj Matešan (Advances in Civil Engineering)
The possibility of the use of a layer of natural material under foundations for seismic base isolation was investigated. The dissipation of seismic energy of a low-cost natural material with adequate thickness, bearing capacity, and lateral and vertical stiffness, which can serve as an optimal solution for seismic base isolation under the foundations of many structures, was tested. This paper presents the results of a brief experimental study to determine the effectiveness of ordinary limestone sand under the foundation of a cantilever concrete column to increase its seismic resistance. The behavior of small-scale columns with three substrates below the foundation (rigid base, the thin layer of limestone sand, and the thick layer of limestone sand) was investigated by the shake table. The column was exposed to a set of horizontal base accelerations until structure collapse. It was concluded that a layer of limestone sand of appropriate thickness and compressibility can serve as the means a seismic base isolation. The nonlinear numerical model for the dynamic analysis of planar concrete structures coupled with soil is briefly presented and verified by the performed experimental tests.